2020
DOI: 10.1142/s0218271820300141
|View full text |Cite
|
Sign up to set email alerts
|

The dark sector cosmology

Abstract: The most important problem in fundamental physics is the description of the contents of the Universe. Today, we know that 95% thereof is totally unknown. Two thirds of that amount is the mysterious Dark Energy described in an interesting and important review [E. J. Copeland, M. Sami and S. Tsujikawa, Int. J. Mod. Phys. D 15 (2006) 1753]. We briefly extend here the ideas contained in that review including the more general Dark Sector, that is, Dark Matter and Dark Energy, eventually composing a new physical Sec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…We note that the nature of interaction function Q is unknown and there is not a unique theoretical model which describes its origin [36][37][38][39]. In terms of phenomenology, there are various approaches in the literature which have shown that a nonzero function Q is supported by the cosmological observations [40][41][42][43][44][45][46][47].…”
Section: Interacting Dark Energymentioning
confidence: 99%
See 1 more Smart Citation
“…We note that the nature of interaction function Q is unknown and there is not a unique theoretical model which describes its origin [36][37][38][39]. In terms of phenomenology, there are various approaches in the literature which have shown that a nonzero function Q is supported by the cosmological observations [40][41][42][43][44][45][46][47].…”
Section: Interacting Dark Energymentioning
confidence: 99%
“…The latter system has been the case of study of various analysis in the literature [49][50][51][52][53][54][55][56][57][58][59][60] where Q = Q (ρ m , ρ d ) has been assumed to be either a linear function [46][47][48][49][61][62][63][64][65][66] and many others. Additionally, with the above choices for the coupling function, various functional forms of the scalar field potential function V (φ) can also be chosen [33,35,[50][51][52]60,[67][68][69][70][71][72].…”
Section: Interacting Dark Energymentioning
confidence: 99%
“…We note that the nature of interaction function Q is unknown and there is not a unique theoretical model which describes its origin [30][31][32]45]. In terms of phenomenology, there are various approaches in the literature which have shown that a nonzero function Q is supported by the cosmological observations [37][38][39][40][41][42][43][44].…”
Section: Interacting Dark Energymentioning
confidence: 99%
“…In recent years new observational results have provided insight into various aspects of general relativity (GR) and cosmology, especially concerning the astonishing contribution provided by dark matter (DM) and dark energy (DE) to the total energy budget of the Universe, contributions that form an overwhelming majority of the mass of the Universe (see, e.g., Abdalla & Marins 2020). Therefore, it is expected that a new physical picture will emerge once more is found about the structure of the dark sector (Abdalla et al 2010;Wang et al 2007Wang et al , 2016.…”
Section: Introductionmentioning
confidence: 99%